Extracellular Matrix and Oxidative Phosphorylation: Important Role in the Regulation of Hypothalamic Function by Gut Microbiota - Qi, Xunzhong; Zhong, Xiaogang; Xu, Shaohua; Zeng, Benhua; Chen, Jianjun; Zang, Guangchao; Zeng, Li; Bai, Shunjie; Zhou, Chanjuan; Wei, Hong; Xie, Peng (Frontiers in Genetics, 2020)
Background In previous studies, our team examined the gut microbiota of healthy individuals and depressed patients using fecal microbiota transplantation of germ-free (GF) mice. Our results showed that depression-like and anxiety-like behavioral phenotypes of host mice were increased, but the molecular mechanism by which gut microbiota regulate host behavioral phenotypes is still unclear. Methods To investigate the molecular mechanism by which gut microbiota regulate host brain function, adult GF mice were colonized with fecal samples derived from healthy control (HC) individuals or patients with major depressive disorder (MDD). Transcriptomic profiling of hypothalamus samples was performed to detect differentially expressed genes (DEGs). qRT-PCR was used for validation experiments. Results Colonization germ-free (CGF) mice had 243 DEGs compared with GF mice. The most enriched KEGG pathways associated with upregulated genes were “protein digestion and absorption,” “extracellular matrix (ECM)-receptor interaction,” and “focal adhesion.” MDD mice had 642 DEGs compared with HC mice. The most enriched KEGG pathways associated with upregulated genes in MDD mice were also “protein digestion and absorption,” “ECM-receptor interaction,” and “focal adhesion.” Meanwhile, the most enriched KEGG pathway associated with downregulated genes in these mice was “oxidative phosphorylation,” and genes related to this pathway were found to be highly correlated in PPI network analysis. Conclusion In summary, our findings suggested that regulation of ECM is a key mechanism shared by different gut microbiota and that inhibition of energy metabolism in the hypothalamus by gut microbiota derived from MDD patients is a potential mechanism of behavioral regulation and depression.